(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
This work focuses on understanding how school motivation and academic commitment are crucial in education, influencing learning. It addresses the relationship between these aspects, emotional intelligence, and academic performance, with a focus on higher education students. The aim is to identify factors that influence motivation. Twelve recent studies were reviewed, finding that intrinsic motivation is essential, but the pandemic and in-person attendance affect motivation. Additionally, the importance of teachers as motivational agents and the need to promote equity in education are highlighted. Emphasizing the need for personalized educational programs, considering socio-emotional well-being. In conclusion, the importance of addressing motivation comprehensively to enhance student engagement and performance in diverse educational contexts is emphasized.